Leadership in Action: Collision Courses: When Social Identity Leads to Conflict - Ohlott, Patricia; Chrobot-Mason, Donna; Dalton, Maxine (Center for Creative Leadership, 2004)
As people with far different social identities increasingly find themselves working together, clashes, differences of opinion, and even serious conflicts are bound to occur. These can have acute consequences for organizations.